Postwar British Economic Growth and the Legacy of Keynes - Cooley, Thomas F.; Ohanian, Lee E. (Journal of Political Economy, 1997)
The policies used by Britain to finance World War II represented a dramatic departure from the policies used to finance earlier wars and were very different from the policies used by the united states during the war. Following Keynes's recommendations, Britain taxed capital income at a much higher rate than the United States during the war and for much of the postwar period. We analyze quantitatively the policies designed by Keneys using an endogenous growth model and the ncoclassical growth model. We also evaluate the implications of tax‐smoothing policies. We find that the welfare costs of Keynes's policies were very high relative to a tax‐smoothing policy and argue that Britain's poor macroeconomic performance in the early postwar period is a consequence of the high tax rates levied on capital income.